« Mais le sablier est devant moi… » (Chateaubriand) - Agnès Verlet (Etudes Epistémè)
Chateaubriand did draw an analogy, even an relationship based on homology, between the genre of vanity painting and the Mémoires d’outre-tombe. Evincing an ambivalent attitude towards mortality, he makes of time the material of an œuvre which he builds like a monument or even an epitaph dedicated to ruins, while his writing voice itself constantly seems on the verge of self-effacement. Keywords : Mémoire d’outre-tombe, Memoirs, monument, epitaph.